2019
DOI: 10.1002/bjs.11076
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section performed by medical doctors and associate clinicians in Sierra Leone

Abstract: Background Many countries lack sufficient medical doctors to provide safe and affordable surgical and emergency obstetric care. Task‐sharing with associate clinicians (ACs) has been suggested to fill this gap. The aim of this study was to assess maternal and neonatal outcomes of caesarean sections performed by ACs and doctors. Methods All nine hospitals in Sierra Leone where both ACs and doctors performed caesarean sections were included in this prospective observational multicentre non‐inferiority study. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…The in-facility perioperative mortality of caesarean section was in line with previous studies in West Africa,31 but higher than the risk of maternal death in some other countries in sub-Saharan Africa, with recorded maternal mortality rates of between 5.43 per 1000 operations in a 2016 prospective cohort study in 22 countries,32 and 10.9 per 1000 in a recent meta-analysis 33. It was also similar to the rate of 1.3% (16 in 1274) recorded among women who underwent caesarean section in nine hospitals in Sierra Leone between October 2016 and May 2017 34. Compared with rates of 0.05% in some high-income countries,35 mortality following caesarean section is about 30 times higher in Sierra Leone.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The in-facility perioperative mortality of caesarean section was in line with previous studies in West Africa,31 but higher than the risk of maternal death in some other countries in sub-Saharan Africa, with recorded maternal mortality rates of between 5.43 per 1000 operations in a 2016 prospective cohort study in 22 countries,32 and 10.9 per 1000 in a recent meta-analysis 33. It was also similar to the rate of 1.3% (16 in 1274) recorded among women who underwent caesarean section in nine hospitals in Sierra Leone between October 2016 and May 2017 34. Compared with rates of 0.05% in some high-income countries,35 mortality following caesarean section is about 30 times higher in Sierra Leone.…”
Section: Discussionsupporting
confidence: 62%
“…Caesarean section has known risks41 of both immediate42–44 and long-term complications,45 and rapid increases in the volume of surgery must be coupled with adequate training of clinicians and robust quality controls, among other interventions 6 11. Indeed, we believe that most of the caesarean sections in this review were performed to save lives—a prospective study of 1274 patients undergoing caesarean section in nine hospitals in Sierra Leone in 2016–2017 showed that most procedures are done as an emergency procedure and on maternal indication34—but clinical audits are needed to ensure caesarean sections are not carried out unnecessarily, and attention should be given to the possibility that the procedure itself may contribute to mortality, in the short and long terms 41…”
Section: Discussionmentioning
confidence: 95%
“…The present study was part of a prospective observational multicenter study of women who underwent cesarean delivery in nine hospitals in Sierra Leone between October 1, 2016, and May 5, 2017. Both associate clinicians and medical doctors performed cesarean deliveries (Table ) . Associate clinicians had completed 2‐year surgical training and the medical doctors were either specialists or non‐specialists.…”
Section: Methodsmentioning
confidence: 99%
“…Sierra Leone has one of the world's poorest perinatal health indicators, with a national cesarean delivery rate of 2.9% and an overall perinatal mortality rate of 39 per 1000 pregnancies . A prospective multicenter study assessing outcomes after cesarean deliveries performed by medical doctors and associate clinicians in Sierra Leone revealed a five times higher perinatal mortality rate (190 per 1000 births [n = 261/1376]) . This finding urged us to explore the causes of this alarmingly high perinatal mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The Commission articulated a broad array of research themes, seven of which are found within the breadth of papers in this supplement including: policy, quality and safety, training and education, partnership, information management, care delivery innovation and burden. However, there are four important themes that are not covered, including cost and finance, determinants and barriers, impact of disease and prevention.…”
mentioning
confidence: 99%